Scolicia and its producer in shallow-marine deposits of the Miocene Chenque Formation (Patagonia, Argentina): functional morphology and implications for understanding burrowing behavior - Carmona, Noelia Beatriz (2020)
Fil: Carmona, Noelia Beatriz. Universidad Nacional de Río Negro. Instituto de Investigación en Paleobiología y Geología. Río Negro; Argentina.